Sustainable use of water hyacinth for community welfare: ecological, economic, and social benefits from PT Pertamina's CSR program at DPPU Adi Sumarmo - Arum Brawijaya Putri; Siti Fathonah; Bintang Fajar Pamungkas (Ethica: International Journal of Humanities and Social Science Studies, 2024)
Water Hyacinth (Eichhornia crassipes) causes negative impacts in the Cengklik Reservoir area because it is considered an invasive weed with very fast growth and ability to spread very efficiently. Although hyacinths have some benefits, there are also significant negative impacts. The existence of wild hyacinths has a negative impact on the tourism sector, accelerating water reduction, fisheries, and fishermen etc. The study aims to investigate the impact and potential use of water hyacinths in sustainability, ecological, economic, and social frameworks, taking into account the principles of Maqashid Sharia. CSR PT Pertamina Patra Niaga DPPU Adi Sumarmo encourages the Community Group of Sobokerto Village, Ngemplak, Boyolali to implement effective management strategies to control the growth of water hyacinths and mitigate their negative impacts by making biogas and organic fertilizer from water hyacinths. The research method used is qualitative, focusing on a deep understanding of people's perceptions and experiences related to hyacinth sustainability. The study found that hyacinth sustainability is not just about achieving favorable economic outcomes, but also respecting the ethical, ecological and social justice principles underlying Maqashid Sharia, so as to provide holistic benefits to the environment and local communities. Thus, hyacinth management can be a positive example in achieving a harmonious balance between environmental sustainability and community welfare in accordance with Islamic teachings. Proper management of hyacinths can maximize their benefits and reduce their negative effects on society and the environment